A study of risk factors for bacteremia caused by urinary tract infections - Varma, Muralidhar; Peravali, Sravan Kumar; KE, Vandana; Kamath, Asha; Singh, Rahul (Asian Journal of Medical Sciences, 2018)
Background: Urinary tract infections are not only one of the most common infections, but also one of the most common sources of bacteremia in both the general population and hospitalized patients. Aims and Objectives: The objective of this study was to identify risk factors for bacteremia caused by urinary tract infections. Materials and Methods: This was a prospective case control study conducted from October 2012 to July 2014in a tertiary care teaching hospital in southern India. Urinary tract infections were diagnosed based on the CDC criteria.Patients witha set of blood cultures and urine culture isolating same organism were grouped as cases while patients with urine culture alone isolating organism with sterile blood cultures were identified as controls. Results: Out of the 198 patientsin the study, 66 were cases while 132 were controls. E coli was the most organism isolated (81% of cases and 66% of controls). Risk factors for bacteremia based on univariate and multivariate analysis were diabetes mellitus with uncontrolled sugars (univariate: p=0.001; OR=5.250 [2.044-13.582]; and multivariate: p=0.01; OR= 6.023 [1.52-23.51]) and pyelonephritis (univariate: p=0.001; OR=6.56 [2.87-1.48]; and multivariate: p=0.047; OR=4.95 [1.02-24.12]). Conclusion: Upper UTI and complicated UTI patients should be evaluated for bacteremia since prompt and targeted treatment may be required. Asian Journal of Medical Sciences Vol.9(5) 2018 25-30